REPRESENTATION OF THE WORD 'REMAJA' IN ONLINE MEDIA: CORPUS-ASSISTED DISCOURSE STUDY - Ayuanda, Winda; Sinar, T. Silvana; Mahriyuni, Mahriyuni (Universitas Negeri Medan, 2024)
Reporting about adolescents in the mass media has a tendency towards criminal acts and delinquent behavior. The aim of this research is to look at the representation of the word 'remaja' in the online media Detikcom from 2022 to 2024 based on a corpus-assisted discourse study. This research uses a mixed approach, with the data source in the form of a corpus composed of Detikcom news articles related to adolescent issues. The corpus has a total number of 325,313 tokens and 26,652 types of words. Through collocation analysis, 45 noun, adjectival, and verbal collocates were taken (15 collocates per word class), which significantly collocated with the word remaja. There are words that explicitly show negative meanings, such as kenakalan, tawuran, gerombolan, mesum, ugal-ugalan, brutal, sadis, mabuk, and tewas. Apart from that, there are also two words that show positive meanings, such as romantis and mengatasi. From the semantic prosody analysis, it can be seen that the word remaja tends to collocate with words that have negative prosody. Based on the concordance lines that have been studied, it was found that there were many crime news that featured adolescents either as perpetrators or as victims of crime. The most frequently found semantic prosody category was negative absolute with 26 collocates, followed by the flexible extremely negative category with 13 collocates. Meanwhile, both the absolute positive and the flexible extremely positive category only have 3 collocates. It can be said that society's view of adolescents is not much different from online media, which is dominated by negative news about adolescents. This ultimately shapes adolescent discourse, which can influence how adolescents are seen and treated in society.